2022
DOI: 10.3390/ijms231911805
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Defatting Strategies for Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease is a huge cause of chronic liver failure around the world. This condition has become more prevalent as rates of metabolic syndrome, type 2 diabetes, and obesity have also escalated. The unfortunate outcome for many people is liver cirrhosis that warrants transplantation or being unable to receive a transplant since many livers are discarded due to high levels of steatosis. Over the past several years, however, a great deal of work has gone into understanding the pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In addition, overexpression of hepatic lipoprotein lipase induces peripheral IR and lipid accumulation [51,57]. Furthermore, models of liver-specific knockdown of fatty acid transporter protein 2 (FATP2) or FATP5 reduce HFD-induced hepatosteatosis and increased glucose tolerance [58,59]. Therefore, our model can also study early molecular mechanisms and dynamics of hepatic steatosis associated with IR.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, overexpression of hepatic lipoprotein lipase induces peripheral IR and lipid accumulation [51,57]. Furthermore, models of liver-specific knockdown of fatty acid transporter protein 2 (FATP2) or FATP5 reduce HFD-induced hepatosteatosis and increased glucose tolerance [58,59]. Therefore, our model can also study early molecular mechanisms and dynamics of hepatic steatosis associated with IR.…”
Section: Discussionmentioning
confidence: 97%
“…Although macrovesicular steatosis is associated with elevated graft failure risk, the impact of this parameter on organ nonuse appears to be disproportionately high [116 ▪ ], despite improvements over time in posttransplant outcomes with steatotic livers [117]. Technological advancements for ‘de-fatting’ livers prior to transplant may hold future promise for improving both utilization and outcomes with these grafts [118]. A recent systematic review found that NMP holds immense potential to recondition and improve evaluation of less-than-ideal liver grafts [119 ▪ ], while remaining cost-effective compared with static cold storage [120].…”
Section: Other Notable Opportunities To Increase Liver Utilizationmentioning
confidence: 99%
“…The recent achievements in tissue engineering of in vitro 2D, 2.5D, 3D, organoid and organ-on-chip ocular models and in vivo and ex vivo ocular models were discussed in terms of their advantages and limitations. Another review by Young et al looks in detail at different strategies for fatty liver treatment in non-alcoholic fatty liver disease [3]. They discuss various defatting strategies, including in vitro use of pharmacologic agents, machine perfusion of extracted livers, and genomic approaches targeting specific proteins.…”
mentioning
confidence: 99%